Rocof-Constrained Solid-State Transformer Frequency Predictive Control - Chavez-Orostica, H; Diaz-Diaz, M; Fuentes-Parra, C; Acosta-Barbosa, K; Riquelme-Vera, E (John Wiley and Sons Inc, 2025)
The increasing integration of power electronic-based generation has significantly weakened power system frequency control due to reduced system inertia. In this context, the load contribution, through its frequency droop and inertia, plays a crucial role in stabilizing frequency fluctuations. However, the integration of solid-state transformers (SST) prevents this contribution from occurring, because the DC-link in the power converters decouples load dynamics from the main grid. Existing solutions attempt to mimic load contributions through synthetic demand responses; they often overlook both to meet grid code requirements and optimize control actions. This paper proposes a predictive frequency control algorithm to maximize load contribution via SSTs, constrained to grid code requirements. The proposal introduces two key innovations: from a transmission perspective, the control formulation is designed to minimize the rate of change of frequency (RoCoF) of the system frequency response; from a distribution feeder perspective, it incorporates constraints on voltage, frequency, and the RoCoF to ensure power quality and prevent the disconnection of distributed generation units (DG). Simulation results are obtained through a model of the involved dynamics, which are compared with a proportional controller. The proposed strategy achieves better performance indicators in all analysed scenarios. © 2025 The Author(s). IET Generation, Transmission & Distribution published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology.